Optimizing Greenhouse Cucumber Fertigation Through Grafting: Improving Yield, Bioactive Compounds, and Antioxidant Activity - Đorđe Vojnović; Ivana Maksimović; Gabrijela Koprivica; Aleksandra Tepić Horecki; Anita Milić; Boris Adamović; Zdravko Šumić; Žarko Ilin (Horticulturae)
Consumers prefer cucumbers (Cucumis sativus) with high antioxidant content, which is often at odds with farmers’ goals of maximizing yield. Therefore, this study aims to explore new methods for fertigation and grafting to optimize the yield and quality of cucumbers. In a greenhouse experiment, we tested fertigation with three different nutrient solutions: the standard as a control (CF) and two new formulations (NF1 and NF2). We also examined grafting in three variants: non-grafted (CG), grafting onto Cucurbita moschata × Cucurbita moschata (G1), and grafting onto Lagenaria siceraria (G2). Our results showed that the highest increase in phenolic content in the flesh of cucumber was observed in the NF2 × G1 treatment (↑ 22.4%). In contrast, grafting and the new fertigation methods generally reduced the phenolic content in the peel. Grafting with G1 significantly increased flavonoid content in the flesh (↑ 59.4% and ↑ 77.3%) but significantly decreased it in the peel. The NF2 × G1 treatment achieved the most significant increases in antioxidant activity indicators, DPPH (↑ 25.9%) and FRAP (↑ 39.4%). For farmers seeking to achieve high yields of greenhouse cucumbers, the combination of NF1 × G1 is recommended, as it resulted in the highest yield increase (↑ 45.3%). Consumers are advised to eat cucumbers with the peel, as this study found higher levels of antioxidant compounds in the peel compared to the flesh.